Psychological states mediate the relationship between sleep quality and frailty among older adults - Su, Huabin; Wei, Liuxiang; Lin, Yanyan; Hu, Caiyou; Lv, Yuan; Li, Hua; He, Xianghua; Zhang, Di; Ni, Xiaolin (Frontiers in Psychology, 2025)
ObjectiveFrailty prevalence is high among older adults. While the association between poor sleep quality and frailty is established, the mediating role of psychological states (anxiety/depression) and the moderating influence of multidimensional factors (physiological conditions, dietary habits, and lifestyle factors) on this pathway remain unclear. This study aimed to examine the mediating effects of anxiety and depression on the sleep quality-frailty link and identify moderators of the sleep quality-psychological state relationship among community-dwelling older adults.MethodsA cross-sectional survey was conducted among 900 adults aged ≥60 years in Dongge Community, Nanning, Guangxi. Sleep quality, anxiety, depression, and frailty were assessed using the Pittsburgh sleep quality index (PSQI), hospital anxiety and depression scale (HADS-A/HADS-D), and FRAIL scale, respectively. Data on physiological conditions, dietary habits, and lifestyle factors were collected via questionnaire. Parallel mediation and moderated mediation analyses were performed.ResultsMean scores were: HADS-A = 1.00 ± 1.76, HADS-D = 1.32 ± 2.11, PSQI = 6.41 ± 3.22, and FRAIL = 0.96 ± 1.05. Parallel mediation analyses confirmed that both anxiety (B = 0.029, 95%CI [0.004, 0.060]) and depression (B = 0.018, 95%CI [0.001, 0.042]) partially mediated the association between poor sleep quality and frailty, collectively accounting for 23.50% of the total effect. Moderated mediation analyses revealed that bodily pain, specific dietary habits (intake frequency ≥5 times/week of milk, soybeans, and fish/meat/eggs), and daily outdoor exercise duration (≥30 min) significantly moderated the strength of the mediating pathway through anxiety (i.e., the “sleep quality → anxiety” link).ConclusionAnxiety and depression significantly mediate the relationship between poor sleep quality and frailty in older adults. Crucially, this mediating pathway via anxiety is modifiable, being attenuated by the absence of bodily pain, frequent consumption of key protein-rich foods, and regular outdoor exercise. These findings highlight potential targets for multi-faceted interventions aimed at mitigating frailty risk by improving sleep and psychological well-being in aging populations.